PENGARUH FORTIFIKASI EKSTRAK PERASAN DAUN KATUK DAN DAUN TORBANGUN TERHADAP KANDUNGAN β-KAROTEN COOKIES UNTUK IBU POSTPARTUM - Kinanti Amela, (2023)
The coverage of vitamin A capsule distribution for postpartum mothers in Indonesia is low and achieving the recommended daily intake of 850 µg RE/day is difficult. β-Carotene, which is found in plants as provitamin A, is more stable than vitamin A and can be found in leaves such as katuk and torbangun. This study is aimed to increase vitamin A intake among postpartum and lactating mothers by analyzing the nutritional content and β-Carotene levels of cookies made from squeezed extract of katuk and torbangun leaves. This study used a Completely Randomized Design (CRD) with five levels of treatment and three repetitions. The chemical analysis included proximate analysis and beta-carotene tests, and data analysis used one-way ANOVA, DMRT, and T-test. The F1 product was found to be the best formulation, with a Product Value of 0.69 and an average β-Carotene content of 4.02 mg/kg. The proportion of katuk and torbangun extract had a significant impact on the ash content, carbohydrate, and beta-carotene content of the cookies (p<0.05), and the T-test showed a significant difference in beta-carotene content between the control and treatment (p<0.05). Further studies are needed to test the effectiveness of the cookies on postpartum mothers.